2022
DOI: 10.3390/molecules27154810
|View full text |Cite
|
Sign up to set email alerts
|

Interdiction in the Early Folding of the p53 DNA-Binding Domain Leads to Its Amyloid-Like Misfolding

Abstract: In this article, we investigate two issues: (a) the initial contact formation events along the folding pathway of the DNA-binding domain of the tumor suppressor protein p53 (core p53); and (b) the intermolecular events leading to its conversion into a prion-like form upon incubation with peptide P8(250-257). In the case of (a), the calculations employ the sequential collapse model (SCM) to identify the segments involved in the initial contact formation events that nucleate the folding pathway. The model predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…induce the aggregation of native α-synuclein. 115 Finally, experiments have also shown that a capped peptide including the segment 71 VTGVTAVAQKTV 82 tends to form β-sheet rich oligomers under prefibrillar conditions. 83 These results, combined with the lack of pathogenic aggregation of truncated α-synuclein, suggest a hypothesis concerning the relationship between nonlocal contact formation and the α-synuclein aggregation and pathogenicity mechanism.…”
Section: Synucleinmentioning
confidence: 99%
See 4 more Smart Citations
“…induce the aggregation of native α-synuclein. 115 Finally, experiments have also shown that a capped peptide including the segment 71 VTGVTAVAQKTV 82 tends to form β-sheet rich oligomers under prefibrillar conditions. 83 These results, combined with the lack of pathogenic aggregation of truncated α-synuclein, suggest a hypothesis concerning the relationship between nonlocal contact formation and the α-synuclein aggregation and pathogenicity mechanism.…”
Section: Synucleinmentioning
confidence: 99%
“…If the hypothesis presented above is correct, a possible FITR/FIP strategy to prevent the pathogenic aggregation of α-synuclein becomes available: Design an interdicting molecule that preferentially binds to segment 70 VVTGV 74 , that through interdiction of the formation of contact 3−72, displaces the nonlocal equilibrium toward the other contacts between the NAC and the C-terminal domains. In principle, the FITR could be either of the pair of the contact-defining native segments 1 MDVFM 5 or 70 VVTGV 74 , but the observed tendency of capped peptides including segment 71 VTGVTA-VAQKTV 82 to form oligomers suggests that 70 VVTGV 74 should not be employed as the basis for the FIP. 117 Thus, the FIP can probably be developed more safely from segment 1 MDVFM 5 .…”
Section: Synucleinmentioning
confidence: 99%
See 3 more Smart Citations